Evaluation of the new UKCA climate-composition model - Part 1: The stratosphere - Morgenstern, O; Braesicke, P; O'Connor, F; Bushell, A; Johnson, C; Osprey, S; Pyle, J (European Geosciences Union, 2009)
The UK Chemistry and Aerosols (UKCA) model is a new aerosol-chemistry model coupled to the Met Office Unified Model capable of simulating composition and climate from the troposphere to the mesosphere. Here we introduce the model and assess its performance with a particular focus on the stratosphere. A 20-year perpetual year-2000 simulation forms the basis of our analysis. We assess basic and derived dynamical and chemical model fields and compare to ERA-40 reanalyses and satellite climatologies. Polar temperatures and the lifetime of the southern polar vortex are well captured, indicating that the model is suitable for assessing the ozone hole. Ozone and long-lived tracers compare favourably to observations. Chemical-dynamical coupling, as evidenced by the anticorrelation between winter-spring northern polar ozone columns and the strength of the polar jet, is also well captured. Remaining problems relate to a warm bias at the tropical tropopause, slow ascent in the tropical pipe with implications for the lifetimes of long-lived species, and a general overestimation of ozone columns in middle and high latitudes.